Intelligent web proxy cache replacement algorithm based on adaptive weight ranking policy via dynamic aging - Olanrewaju, Rashidah Funke; Al-Qudah, Dua'a Mahmoud Mohammad; Azman, Amelia Wong; Yaacob, Mashkuri (2016)
Rapid growth in network services and vast usage of Internet worldwide have led to an increase in network traffic and created bottleneck over the internet. Such traffic results in an increase of access time of web documents, server response latency, reduced network bandwidth and slow response time for popular websites. Web cache is an essential optimization technique used to reduce response time and improve performance. However due to its limited size and cost of cache comparable to other storage devices, cache replacement algorithm is used to determine and evict page when the cache is full to create space for new pages. Several algorithms had been introduced and their performances are important in producing high speed web caching. However, their performances are not well optimized. This work proposes a hybrid method that optimize cache replacement algorithm using Naïve Bayes (NB) based approach. Naïve Bayes is an intelligent method that depends on Bayes’ probability theory integrated with Adaptive Weight Ranking Policy (AWRP) via dynamic aging factor to improve the response time and network performance. From the pseudocode of the proposed algorithm, it is observed that the complexity of the algorithm is O(n) which is linear, hence the response time is considered good. Performance evaluations based on hit rate and byte hit rate for the new method over conventional methods with real data will be conducted for validation and verification